Study guides

Q: What is -2a - 9 equals 39?

Write your answer...

Submit

Related questions

2a + 9 = 4a - 19 9 + 19 = 4a - 2a 28 = 2a a = 14

2a - 7 = -9 2a - 7 + 7 = -9 + 7 2a = -9 +7 2a = -2 2a/2 = -2/2 a = -2/2 a= -1

-7a+2a+9 is also -5a+9. -5a+9=24. -5a=15. a=-3.

2a - 1 = 9 Therefore, 2a = 10 a = 10/2 = 5 Therefore, a = 5.

(4, 3)

Simple algebra, 2a-20 = -2 2a=18 a=18/2 a=9

a + a + a - 2a = 3a - 2a = a

2*9 - 5 = 18 - 5 = 13

5a-20+2a = 6a-11 5a+2a-6a = 20-11 1a = 9 a = 9

the answer

4

6

It is the expression 3 + 2a.

a= (+a) or a= (-) b= 2a b= 2a c= (-a) c= (+a)

1

eleven! doo doo doo doot

a = 26

2a 4 is the same as saying 2*a*4, so if you plug 2 in for a, this equals 16

A equals 20.

2a+5a+9a = 16a

3.5

Subtract 2a from each side: P - 2a = b ie b = P - 2a

assuming 5a-a-2a-18=0 2a-18=0 2a=18 and thus a=9

3a x 2a =24

2a + 21 = 8a - 9Add 9 to each side:2a + 30 = 8aSubtract 2a from each side:30 = 6aDivide each side by 6:5 = a